Czy inwestowanie za granicą jest niepatriotyczne? Miejsca pracy i inwestycje w rozszerzającej się Unii Europejskiej - Prinz, Aloys (Is Investing Abroad Unpatriotic? Jobs and Investments in an Expanding EU, 2006)
The author Starts his paper with presenting a thesis (being not shared by him, however) that if investing abroad, and especially in EU member countries, is profitable but it results in losing domestic jobs, such foreign activity may be considered "unpatriotic". He highlights this thesis in a more complex context of globalization and European integration. In the first section, some basic facts concerning German foreign investments are presented which is followed by answering the question why foreign investments take place. It includes specific effects of globalization and the EU eastward enlargement. In the subsequent part of the paper the dynamics of product cycles are taken into account to explain why a country investing abroad might loose whole domestic industries without losing domestic jobs. While analyzing labor market consequences of foreign investments, the author also refers to the effects of globalization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1138, s. 28-42